The Influence Of Agency Services And Business Strategy On Customer Satisfaction At PT. Bahari Eka Nusantara Representative Ben Line Agencies Indonesia - Agung Kwartama; Alexandros Siringo Ringo (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The obstacles that PT. Bahari Eka Nusantara in increasing the number of customers has difficulty providing satisfaction to customers and the ship's crew itself and inaccuracies in registering when ships arrive and depart, resulting in high costs waiting for service schedules. The existence of PT. Bahari Eka Nusantara as a representative of Ben Line Agencies specifically shows recognition of Indonesia's maritime potential and commitment to establishing strong cooperation in supporting the growth of this sector at the national level. The formulation and aim of this research is to determine and analyze the influence of agency services and business strategy on customer satisfaction at PT. Bahari Eka Nusantara Representative of Ben Line Agencies Indonesia, especially the Jakarta branch. The analysis technique used in the research is a survey method with quantitative research through distributing questionnaires as primary data. With a sample of 77 customer respondents who are agents of PT. Bahari Eka Nusantara Representative of Ben Line Agencies Indonesia, especially the Jakarta branch. The research results show that there is a positive and significant influence of agency services on customer satisfaction at PT. Bahari Eka Nusantara Representative of Ben Line Agencies Indonesia, there is a positive and significant influence of business strategy on customer satisfaction at PT. Bahari Eka Nusantara Representative of Ben Line Agencies Indonesia and there is a positive and significant influence of agency services and business strategy simultaneously on customer satisfaction at PT. Bahari Eka Nusantara Representative of Ben Line Agencies Indonesia. It can be concluded that directly or simultaneously there is a positive and significant influence of agency services and business strategy on customer satisfaction at PT. Bahari Eka Nusantara Representative of Ben Line Agencies Indonesia